Homologous Recombination Deficiency in Ovarian, Breast, Colorectal, Pancreatic, Non-Small Cell Lung and Prostate Cancers, and the Mechanisms of Resistance to PARP Inhibitors - Mekonnen, Negesse; Yang, Hobin; Shin, Young Kee (Frontiers in Oncology, 2022)
Homologous recombination (HR) is a highly conserved DNA repair mechanism that protects cells from exogenous and endogenous DNA damage. Breast cancer 1 (BRCA1) and breast cancer 2 (BRCA2) play an important role in the HR repair pathway by interacting with other DNA repair proteins such as Fanconi anemia (FA) proteins, ATM, RAD51, PALB2, MRE11A, RAD50, and NBN. These pathways are frequently aberrant in cancer, leading to the accumulation of DNA damage and genomic instability known as homologous recombination deficiency (HRD). HRD can be caused by chromosomal and subchromosomal aberrations, as well as by epigenetic inactivation of tumor suppressor gene promoters. Deficiency in one or more HR genes increases the risk of many malignancies. Another conserved mechanism involved in the repair of DNA single-strand breaks (SSBs) is base excision repair, in which poly (ADP-ribose) polymerase (PARP) enzymes play an important role. PARP inhibitors (PARPIs) convert SSBs to more cytotoxic double-strand breaks, which are repaired in HR-proficient cells, but remain unrepaired in HRD. The blockade of both HR and base excision repair pathways is the basis of PARPI therapy. The use of PARPIs can be expanded to sporadic cancers displaying the “BRCAness” phenotype. Although PARPIs are effective in many cancers, their efficacy is limited by the development of resistance. In this review, we summarize the prevalence of HRD due to mutation, loss of heterozygosity, and promoter hypermethylation of 35 DNA repair genes in ovarian, breast, colorectal, pancreatic, non-small cell lung cancer, and prostate cancer. The underlying mechanisms and strategies to overcome PARPI resistance are also discussed.